O ensino do futevôlei na educação física escolar: criação de uma cartilha para professores - Thalles Costa Ferreira (2023)
Observing the current scene, one notices the great increase of outdoor sports practices, well impressed by the new Coronavirus pandemic. People were restricted from their free will to come and go for a period, and as soon as urban mobility restrictions were being relaxed, there was a lot of demand for these modalities due to the fact that it was not in a closed environment. And so, footvolley emerges as an escape valve in the pursuit of health promotion, involving biological, psychological, social, cultural and environmental well-being. The present study aimed to develop and evaluate an educational booklet on footvolley for physical education teachers. The methodology was based on a qualitative study through the application of a questionnaire, with semi-open, open and closed questions whose analysis was proposed by Bardin (2004). The sample consisted of 13 teachers from the second group of the Professional Master's Program in Physical Education in the National Network (ProEF), linked to the UFMG pole. The research was motivated by the lack of studies relating footvolley to school Physical Education, by the significant increase in the number of practitioners in recent years and the interest of students in learning about the modality. Data analysis and research results prove the importance of having specific footvolley material so that teachers can use it as a basis within their pedagogical proposal. It is noteworthy the relevant purpose that this study and its final product may have for the field of Physical Education for being a pioneer in thematizing footvolley in the educational environment.